Innovation in the Digitalization of the Sijapati Application as a Medium for Performance Management of the Civil Service - Nadya Salsabilla Stephanie; Siti Khumayah (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
Digitalization of the performance management of the State Civil Apparatus (ASN) is an important need to increase the effectiveness, transparency, and accountability of performance in the public sector. However, the implementation of digital innovation is often faced with user acceptance challenges and technical constraints. This study aims to analyze the development and implementation process of the SIJAPATI application developed by the Kuningan Regency Personnel and Human Resources Development Agency (BKPSDM), identify the factors that affect its acceptance and utilization, and examine the obstacles faced in its implementation. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation, and uses the theory of Diffusion of Innovation by Rogers (1983), which includes five characteristics of innovation, namely relative advantage, compatibility, complexity, trialability, and observability. The results of the study show that the development and implementation of SIJAPATI is carried out in stages through trials, socialization, and continuous evaluation. SIJAPATI acceptance is influenced by relative advantage in the form of ease of performance reporting, system conformity with ASN regulations and work needs, trial opportunities before full implementation, and visibility of performance results that can be monitored directly. Implementation obstacles mainly arise in the early stages in the form of technical obstacles and user adaptation processes, but they are temporary. This study concludes that SIJAPATI is effective as a digital innovation in supporting the management of ASN performance within the Kuningan Regency government.